The living wage crisis in Australian industrial relations. (2nd October 2017) - Thornthwaite, Louise
ABSTRACT: The recent proliferation in Australia of systematic wage underpayment, or wage theft as it is known in the US, is stripping workers of the 'living wage', once a cornerstone of Australia's industrial relations system. This paper considers the dimensions of this phenomenon and some of the policy recommendations for regulatory reform to reduce employer non-compliance with minimum wage standards. The paper concludes with proposals for other measures that may also help arrest what is becoming a living wage crisis and restore fair and reasonable wages to workers, regardless of employment arrangement or status. 1